Influence of different safety shoes on gait and plantar pressure: a standardized examination of workers in the automotive industry. Issue 5 (30th September 2016) - Ochsmann, Elke; Noll, Ulrike; Ellegast, Rolf; Hermanns, Ingo; Kraus, Thomas
Abstract : Objective: Working conditions, such as walking and standing on hard surfaces, can increase the development of musculoskeletal complaints. At the interface between flooring and musculoskeletal system, safety shoes may play an important role in the well‐being of employees. The aim of this study was to evaluate the effects of different safety shoes on gait and plantar pressure distributions on industrial flooring. Methods: Twenty automotive workers were individually fitted out with three different pairs of safety shoes ("normal" shoes, cushioned shoes, and midfoot bearing shoes) . They walked at a given speed of 1.5 m/s. The CUELA measuring system and shoe insoles were used for gait analysis and plantar pressure measurements, respectively. Statistical analysis was conducted by ANOVA analysis for repeated measures. Results: Walking with cushioned safety shoes or a midfoot bearing safety shoe led to a significant decrease of the average trunk inclination (p< 0.005). Furthermore, the average hip flexion angle decreased for cushioned shoes as well as midfoot bearing shoes (p<0.002). The range of motion of the knee joint increased for cushioned shoes. As expected, plantar pressure distributions varied significantly between cushioned or midfoot bearing shoes and shoes without ergonomic components. Conclusion: The overall function of safety shoes is the avoidance of injury in case of an industrial accident, but in addition, safety shoes could be a long‐term preventive instrument for maintaining health of the employees' musculoskeletal system, as they are able to affect gait parameters. Further research needs to focus on safety shoes in working situations.